1998
DOI: 10.1902/jop.1998.69.4.445
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Microbiological Evaluation of a Bioabsorbable and a Nonresorbable Barrier Membrane in the Treatment of Periodontal Intraosseous Lesions

Abstract: Clinical and microbiological features of periodontal healing in barrier membrane‐treated sites were determined in a randomized clinical trial. The study included 10 patients with advanced adult periodontitis and a minimum of one set of similar 2 to 3 wall intraosseous periodontal lesions with no furcation involvement. In each patient, one periodontal lesion was treated with a biodegradable membrane and a contralateral lesion with a nonresorbable barrier membrane. Within the preceding 3 months of regenerative t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
44
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 51 publications
1
44
0
Order By: Relevance
“…In recent years, evidence has indicated that the presence of a pathogenic flora at the regenerated site or in the oral cavity of the patient before, during or after periodontal regeneration was associated with compromised outcomes (Smith MacDonald et al, 1998;Heitz-Mayfield et al, 2006). These pathogens influence and disrupt the blood clot in the early stages of healing and affect the amount of new tissue formation.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, evidence has indicated that the presence of a pathogenic flora at the regenerated site or in the oral cavity of the patient before, during or after periodontal regeneration was associated with compromised outcomes (Smith MacDonald et al, 1998;Heitz-Mayfield et al, 2006). These pathogens influence and disrupt the blood clot in the early stages of healing and affect the amount of new tissue formation.…”
Section: Introductionmentioning
confidence: 99%
“…wound healing potential, immune system, oral hygiene, defect morphology, smoking habits) (Tonetti et al 1995, Kornman & Robertson 2000, Cortellini & Tonetti 2000, there is strong evidence that membrane specific problems (e.g. Although the strict plaque control regimens of previous controlled clinical studies appeared to prevent a harmful effect of postoperative membrane exposures on the attachment gain (Becker et al 1996, Christgau et al 1997b, membrane exposures dramatically increase the risk for bacterial contamination and penetration of the exposed membrane parts (Grevstad & Leknes 1993, Nowzari et al 1995, Nowzari et al 1996, Chen et al 1997, MacDonald et al 1998). Bacterial contamination of the membranes can have a detrimental effect on the periodontal regeneration (Nowzari et al 1995, Slots et al 1999.…”
mentioning
confidence: 99%
“…A clinical attachment gain <3 mm or even a loss of attachment was noted when the bacterial count on the GTR membrane was >10 8 in vivo 10 . Membrane bacterial count is positively associated with gingival recession 16 and is negatively associated with clinical attachment gain 8,11,12,17‐20 . These studies indicated the importance of controlling or eliminating periodontal pathogens during GTR procedures.…”
mentioning
confidence: 83%
“…Bacterial contamination of the regenerating wound represents the most significant factor leading to a compromised outcome 5–7 . Bacterial species, 8,9 bacterial count, 9,10 and the area of bacterial contamination present on the GTR membrane 11,12 are some of the factors that may affect GTR outcome. The bacteria found on GTR membranes include various Gram‐positive bacteria as well as periodontal pathogens 13 .…”
mentioning
confidence: 99%